An Outbreak of Aspergillus Species in Response to Environmental Conditions in Serbia - LEVIĆ, JELENA; GOŠIČ-DONDO, SNEŽANA; IVANOVIĆ, DRAGICA; STANKOVIĆ, SLAVICA; KRNJAJA, VESNA; BOČAROV-STANČIĆ, ALEKSANDRA; STEPANIĆ, ANA (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The frequency and incidence of A. flavus and A. niger on barley, maize, soybean, sunflower and wheat grain, the abundance of European corn borer (Ostrinia nubilalis) moths and their interaction depending on weather conditions in the 2008-2012 period were studied. Under the agroecological conditions of Serbia, the species A. niger is more frequent than A. flavus, and concerning the crop species, its frequency is highest in kernels of sunflower, than soybean, maize, barley and wheat. A. flavus was extremely dominant on all plant species in 2012 regarding its frequency: 100% on soybean, 95.3% on maize, 65.0% on barley, 57.1% on sunflower and 45.8% on wheat. Furthermore, the incidence of A. flavus was higher in 2012 than in previous years. The uncommonly high frequency and incidence of A. flavus infestation of maize grain in 2012 were caused by extremely stressful agrometeorological conditions, high temperatures and drought over the period from flowering to waxy maturity of maize. The precipitation factor (Pf = precipitation sum / average monthly temperature) showed that 2012 was extremely arid in June (Pf = 0.57), July (Pf = 1.45), August (Pf = 0.15) and September (Pf = 1.42). European corn borer (ECB) was a second factor causing intensive occurrence of A. flavus on maize grain in 2012. The maximum flight of ECB moths was recorded as early as in July (5,149) and, as a result of this, high damage and numerous injuries were detected at harvest. Those injuries were covered by visible olive-green powdery colonies typical of A. flavus. In the chronology of A. flavus occurrence, these are the first data on its very high frequency and incidence under the agroecological conditions of Serbia. As intensive infections with A. flavus were rare in the past 50 years, the level of aflatoxins in maize grain was low.